Correlating Abdominal Wall Thickness and Body Mass Index to Predict Usefulness of Right Lower Quadrant Ultrasound for Evaluation of Pediatric Appendicitis. Issue 3 (March 2020) - Kwon, Jeannie K.; Trexler, Nowice; Reisch, Joan; Pfeifer, Cory M.; Ginos, Jason; Powell, Jerry Allen; Veltkamp, Jennifer; Anene, Alvin; Fernandes, Neil; Chen, Li Ern
Abstract : Objectives: To inform selective and efficient use of appendix ultrasound (US) beyond adult parameters of body mass index (BMI) of less than 25 kg/m 2, we correlate abdominal wall thickness (AWT) with age and BMI to generate parameters for male and female children. Information presented in chart format can aid in the decision to utilize US for the evaluation of appendicitis. Methods: In this observational study, 1600 pediatric computed tomography scans of the abdomen and pelvis were analyzed to obtain measurements of AWT in the right lower quadrant. Measurements were correlated by patient age, BMI, and sex. Results and consensus-based recommendations were presented in chart format with color-coded groupings to allow for convenient referencing in the clinical setting. Results: One thousand four hundred eighty-eight computed tomography scans and AWT measurements were included. All age groups with BMI of less than 25 kg/m 2 and all male and female groups younger than 6 years regardless of BMI had median AWT of less than 4 cm resulting in strong recommendation for US. Males older than 6 years and all female age groups with BMI of greater than 30 kg/m 2 and female older than 15 years and BMI of greater than 25 kg/m 2 had AWT of more than 5 cm resulting in low recommendation for US. Conclusions: While the BMI cutoff standard of less than 25 kg/m 2 for usefulness of appendix US holds in the adult population, our data expand the acceptable range in children younger than 9 years regardless of BMI and male children with BMI up to 30 kg/m 2 . Female children younger than 15 years with a BMI up to 30 kg/m 2 may also be amenable to right lower quadrant US based on AWT. These parameters inform selective and efficient use of US for appendix evaluation.